Meningkatkan Keterampilan Sosial Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Pair Checks - Arsyad, Ashadi; Hartini, Sri (Universitas Lambung Mangkurat, 2014)
The low social skills of students in class VIII-C of Junior High School 27 Banjarmasin becomes the background of this classroom action research (CAR). The purpose of this research is to examine students social skills improvement by employing the âPair Checksâ cooperative learning model which are carried out in 3 cycles. Method of data collection uses observation sheet ofapplied lesson plans, students social skills, achievement test and student questionnaire responses. The technique of Data Analysis used descriptive quantitative and qualitative techniques. The findings of the study are: (1) the ability of teachers to manage Pair Checks cooperative models the first cycle was 86%, while the second cycle resulted in 87%, and 90%Â in the third cycle, (2) social skills of students has risen that was 90.6% for the first cycle, 91% for the second cycle andÂ 95.6% for the third cycle, (3) mastery learning outcomes of students was 67% of the first cycle, 83%Â for the second cycle and 93% for the third cycle, (4) the response of students to the learning process is good. From the findings above, it can be concluded that the application of Pair Checks cooperative learning model on the subject of light reflection in class VIII C of Junior High School 27 Banjarmasin is effective to improve students social skills.